Glycerophosphocholine and Glycerophosphoethanolamine Are Not the Main Sources of the In Vivo31P MRS Phosphodiester Signals from Healthy Fibroglandular Breast Tissue at 7 T - van der Kemp, Wybe J. M.; Stehouwer, Bertine L.; Runge, Jurgen H.; Wijnen, Jannie P.; Nederveen, Aart J.; Luijten, Peter R.; Klomp, Dennis W. J. (Frontiers in Oncology, 2016)
Purpose The identification of the phosphodiester (PDE) 31P MR signals in the healthy human breast at ultra-high field. Methods In vivo31P MRS measurements at 7 T of the PDE signals in the breast were performed investigating the chemical shifts, the transverse- and the longitudinal relaxation times. Chemical shifts and transverse relaxation times were compared with non-ambiguous PDE signals from the liver. Results The chemical shifts of the PDE signals are shifted −0.5 ppm with respect to glycerophosphocholine (GPC) and glycerophosphoethanolamine (GPE), and the transverse and longitudinal relaxation times for these signals are a factor 3 to 4 shorter than expected for aqueous GPC and GPE. Conclusion The available experimental evidence suggests that GPC and GPE are not the main source of the PDE signals measured in fibroglandular breast tissue at 7 T. These signals may predominantly originate from mobile phospholipids.